Pengaruh Kinerja Keuangan dan Ukuran Perusahaan terhadap Nilai Perusahaan Manufaktur Sektor Industri yang Terdaftar di BEI - Sevina, Fanreza Budi; Nugraeni, Nugraeni (ITB AAS Indonesia Surakarta, 2024)
This study aims to determine the effect of Financial Performance and Company Siz e on the value of industrial sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2023. Financial Performance is measured by Return On Equity (ROE), Current Ratio (CR), Debt to Equity Ratio (DER), Company Size and Company Value as measured by Price Earning Ratio (PER). The research method used is multiple linear regression analysis. This type of research is quantitative research. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2023, totaling 69 companies. By using purposive sampling technique and obtained a sample of 16 companies with a research period of 3 years, resulting in 48 research sample data. The results of this study partially show that the Roe and Der variables have a positive and significant effect on firm value, while the CR and company size variables have a negative and insignificant effect on firm value.